Psoriatic arthritis: An up to date overview - Simon Hackett; Laura Coates (Indian Journal of Rheumatology)
Psoriatic arthritis (PsA) is a chronic, systemic inflammatory arthritis with symptoms spanning six domains including peripheral arthritis, enthesitis, dactylitis, axial disease, psoriasis, and nail disease. The classification of disease has been refined over recent years following the development of criteria such as ClASsification of PsA criteria. In addition to classification, treatment options for PsA have continued to expand over recent years, with the development of monoclonal antibody therapies targeting the underlying immunological mediators involved in PsA such as interleukin (IL)-17, tumor necrosis factor-alpha, and IL-23. Therapies have shown that robust treatment in patients, achieving tight disease control, improves outcomes and overall quality of life. This review provides a broad overview of the epidemiology, classification, and treatment of PsA.